Low-Cost Carrier Passengers’ Willingness to Pay for the Seat Preselection Service: A Case Study on the Taiwan-Japan Route - Rong-Chang Jou; Yi-Chun Chiu; Chung-Wei Kuo (Journal of Advanced Transportation)
Due to the rising of consumer awareness, consumers not just pay more attention to leisure activities but also demand more on the related service quality. In recent years, low-cost carriers (LCCs) have continued to expand their routes, and traditional aviation is no longer the only choice for travel abroad. Different from the traditional way of operation, LCCs focus on reducing nonessential expenses. The concept of payment by service offers passengers the options for relatively low ticket price. To continuously operate in the highly competitive aviation industry, most airlines have introduced distinctive “value-added additional services” to attract air passengers. This study discusses the seat preselection, value-added service, and behavior of Taiwanese passengers who take low-cost flights to Japan. The results indicate that passengers who have experienced purchasing preselected seats are more willing to purchase this additional service and spend higher amount of money for that service. In addition, the result also indicates that younger people are more willing to accept novel services. These findings could be used as an importance reference for LCCs to guide managerial strategy in the future.